It is B, the coefficient of the x-term. When you multiply this out, you get x*x+x*q+x*p+p*q, or x^2+x(p+q)+p*q
Notice how the x term is multiplied by p+q.
Hope this helps!
Answer:
A. 2x + (-x + 2) = -1
Step-by-step explanation:
Well if we use x + y = 2 as the substitute we need to solve for y.
x + y = 2
-x to both sides
<u>y = -x + 2</u>
Substitute
2x + (-x + 2) = -1
<em>Thus,</em>
<em>the answer is A. 2x + (-x + 2) = -1.</em>
<em />
<em>Hope this helps :)</em>
The airplane is 48 feet long in real dimensions.
To find out how long the airplane actually is, we can use the scale and input our amount of inches that it is measured by.
So, 1 inch equals to 6 feet.
Our model plane is 8 inches.
Now, we plug it in.
8 inches = 6(8)
8 inches = 48 feet
Therefore, the length of the real airplane is 48 feet.
48 feet
Answer:
3/2
Step-by-step explanation:
Answer:
When raising an expression of that format to any power, after grouping like terms, you'll always find that the odd numbered terms are positive, and the even numbered terms are negative.
For example:
(x - y)² = x² − 2xy + y²
(x - y)³ = x³ − 3x²y + 3xy² − y³
(x - y)⁴ =x⁴ − 4x³y + 6x²y² − 4xy³ + y⁴
etc.